Implementasi Kebijakan Pemberdayaan Lansia Program PKH Plus di Dinas Sosial Provinsi Jawa Timur - Kharima, Evianti; Nawangsari, Ertien Rining (IAI Nasional Laa Roiba Bogor, 2024)
The government has attempted various programs to improve the welfare of the elderly, but there are still many cases related to the elderly, so assistance is needed from various parties to jointly help the government develop more innovative efforts to improve the welfare of the elderly. This research aims to understand how the implementation of the PKH Plus social assistance program meets the needs of elderly beneficiaries and creates better behavioral changes, poverty alleviation, and increases the standard of living of the elderly. This research uses a qualitative descriptive research method. Data collection used in this research was based on observation and interview techniques. Data analysis techniques include data reduction, data presentation, and drawing conclusions or data verification. The research results show that the implementation of the PKH Plus program by the East Java Provincial Social Service has contributed to the success of improving the welfare conditions of the elderly in the districts/cities receiving assistance.